Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/dech.12082
|View full text |Cite
|
Sign up to set email alerts
|

When Governance Gets Going: Certifying ‘Better Cotton’ and ‘Better Sugarcane’

Abstract: As many new certification systems for commodities have been established over the past decade, scholars have devoted sustained attention to the ways that these multi‐stakeholder governance initiatives have transformed the industries in which they were launched. With a few notable exceptions, studies in this area have continued to focus on the development and impacts of new governance mechanisms, and on the sectoral or industrial changes that have ensued. In contrast to these ‘inside‐out’ perspectives on governa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Scholars have emphasized the risks and opportunities of private certification [7,21,24,33]. We found that certification according to the EU Organic Regulation manifests the international agenda-setting of environmental sustainability, while social aspects of water sustainability remain hidden.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Scholars have emphasized the risks and opportunities of private certification [7,21,24,33]. We found that certification according to the EU Organic Regulation manifests the international agenda-setting of environmental sustainability, while social aspects of water sustainability remain hidden.…”
Section: Discussionmentioning
confidence: 95%
“…The Better Cotton Initiative (BCI) and Cotton made in Africa (CmiA) are the most dominant schemes certifying cotton cultivation, based on the number of producers and volume of cotton certified. Producers who qualify for the CmiA certification are able to market their cotton as both BCI and CmiA [21,48].…”
Section: Case Studies: Voluntary Cotton/textiles Certificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting with bananas, the organization has since carried its model to other commodities from coffee to cattle. The World Wide Fund for Nature (WWF, or World Wildlife Fund in the USA) followed a similar logic; after experiences with forestry, it helped establish the Roundtable on Sustainable Palm Oil (RSPO) (Schouten and Glasbergen 2011), the Round Table of Responsible Soy (RTRS) (Elgert 2012) and, most recently, Bonsucro and Better Cotton Initiative (BCI) (Sneyd 2014). Foundations, international organizations, government development agencies, auditors and large retailers have also been identified as carriers of certification, meaning that their existence in a network is seen to play an important role in expanding the formation of TPGOs.…”
Section: Transnational Private Governance Organizations: From Interacmentioning
confidence: 99%
“…Foundations, international organizations, government development agencies, auditors and large retailers have also been identified as carriers of certification, meaning that their existence in a network is seen to play an important role in expanding the formation of TPGOs. Examples of such agencies are, respectively, the Packard Foundation for the Roundtable for Sustainable Biofuels (Ponte 2014), the World Bank for the foundation of BCI and Bonsucro (Sneyd 2014), the German Development Corporation for the Common Code for the Coffee Community or 4C , SGS for Social Accountability International (Auld et al 2007) and the Dutch retailer Ahold, which helped establish Utz (Auld 2010).…”
Section: Transnational Private Governance Organizations: From Interacmentioning
confidence: 99%